Comparison of Variation of Vitamin C Content with Ripening Stages in Fruit Extracts of Solanum Gilo, Solanum Anguivi And Solanum Aculeastrum. - Ayebare, Happiness (Kabale University, 2024)
Investigation of change in the amount of vitamin C in S. aculeastrum, S. anguivi, and S. gila as a result of ripening time involved titration of aqueous extracts from green, yellow, and red fruits separately using potassium iodate. The results obtained showed the content of vitamin C in green fruits which varied as follows; aculeastrum: 0.0088M, S.anguivi: 0.0077M, and S. gila: 0.0061M. The yellow fruits had S. aculeastrum: 0.0073M, S. anguivi: 0.0062M, and S. gilo: 0.0046M, and red fruits had S. aculeastrum: 0.0058M, S. anguivi: 0.0047M, and S. glo: 0.0003M. The data revealed a decrease in the concentration of vitamin C in fruits that turned green from yellow to red. In dietary terms, these fruits should be consumed when green because in that form they contain the highest concentration of vitamin C.